CONTRIBUIÇÕES DO SCRATCH NA RESOLUÇÃO DE SITUAÇÕES-PROBLEMAS QUE ENVOLVEM ANÁLISE COMBINATÓRIA - Nunes, Lucas Linke (2024)
This dissertation is part of the research line “Teaching and Learning of Science and Mathematics”, of the Graduate Science and Mathematics Teaching Program (PPGECIMAT), of the Franciscan University (UFN). It is common for students to have great difficulties in learning Combinatorial Analysis, both in understanding the definitions and in interpreting problem situations. To this end, there are strategies that can help in this process, among them, we believe that the use of Digital Information and Communication Technologies (TDIC) can be an interesting choice. After all, these are part of contemporary society and their use in teaching is becoming increasingly necessary. Therefore, this research intends to analyze the Scratch software contributions in problem solving situations involving Combinatorial Analysis. The subjects for the research were second-year high school students from a public school in São João do Polêsine, RS. To this end, we developed a Learning Unit (UA), divided into five encounters, organized according to the Three Pedagogical Moments methodology. In this UA, first we investigated the students' prior knowledge about Combinatorial Analysis and the use of the Scratch software; in the second moment, the definitions of Combinatorial Analysis were reviewed, and the participants solved activities in Scratch, finally, to identify the students' learning, they produced activities in Scratch. The research approach was mixed, of the case study type, and the data were analyzed using the content analysis technique (qualitative data) and with the Wilcoxon test and the Binomial Test for proportions (quantitative data). This research resulted in a significant increase in the participants' performance and contributed to the development of their computational thinking.